Pengaruh Kualitas Pelayanan, Produk dan Harga terhadap Kepuasan Konsumen Pada Shopee - Nelisa Nelisa; Winda Evyanto (Universitas Batanghari, 2022)
In an era that is growing and increasingly sophisticated and the development of internet technology is increasingly rapidly resulting in a higher number of internet users. The internet is commonly used as a communication tool and a tool for finding information, online shopping, entertainment and a place to do business. The purposse for the studying wass to determiine and analyze the effect for Service Qualiity, Product Price for Consumer Satisfactiion at Shopee. Thee population in this study were people who used the website Shopee with a samplee of 385 resspondents who were seleected usiing the Purposiive Sampliing techniq. Primary data collection using a questionaire. The analysis data method used this studyis quantiitative analysis and uses descriptive statistical test, classical assumptiion tests, multiplee linear regression test, and hypothesis testing and coefficient of determination (R2) testing. The result of the study prove the quality of service, product and price can have a positive and significant effect on customer satisfaction with shopee users.